Q. 4 F4.5( 11 Votes )

<span lang="EN-US

Answer :

In the given expression

We know that


(a + b)2 = a2 + 2ab + b2


(a-b)2 = a2-2ab + b2


Hence


4[a2 + 2ab + b2] – 9[a2-2ab + b2]


4a2 + 8ab + 4b2 - 9a2 + 18ab - 9b2


26ab – 5a2 - 5b2


25ab + ab – 5a2 – 5b2


[25ab – 5a2] + [ab – 5b2]


5a[5b – a] – b[5b – a]


[5a – b][5b – a]


Hence the factors 4 (a + b)2 – 9 (a – b)2 are [5a – b] and [5b – a]


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics